The Prosecutor in your pocket: a study on the constitutional issues arising out of the use of social media evidence in government investigations with a specific focus on the right to privacy - Muigai, Kena Michael (Strathmore University, 2016)
Today, individuals network and interact with each other in radically different ways, using social networking sites such as Facebook and Twitter. Utilizing this new media, individuals are able to share intimate details of their lives, coordinate activities, and exchange ideas with friends, family and others in ways previously accomplished only in person, by telephone, or in written letters stored in one 's home. At the same time, social networking sites are increasingly being utilized by terrorist entities for both recruiting purposes and for the planning, financing , and execution of terrorist acts, as well as by other criminal actors. As such social networks have become a valuable source of intelligence for the law enforcement and intelligence communities, enabling the collection of information pertaining to individuals in ways not previously possible. However, the law pertaining to surveillance in cyberspace has failed to keep pace with society's adoption of social networking and other cloud computing technologies. This paper examines the privacy safeguards inherent in the article 31 of the Kenyan Constitution 2010 and Fourth Amendment to the American Constitution and the need to strike an appropriate balance between an individual 's reasonable expectations of privacy in one's online communications and the government's intelligence requirements necessary to combat emerging criminal and terrorist threats.
Full text